Гуцульщина у поезії Христі Алчевської - Васильчук, М. (Україна: культурна спадщина, національна свідомість, державність, 2012)
Статтю присвячено вивченню гуцульських тем і мотивів у творчості української письменниці першої третини ХХ ст. Христі Алчевської (1882–1931). Показано як відобразилась на світобаченні письменниці поїздка в Карпати 1906 р.; наведено факти зближення представників різних регіонів України на ґрунті національної літератури. Окреслено взаємини авторки з Іваном Франком, Михайлом Павликом, Ольгою Кобилянською. The article is devoted to Hutsul themes and motive studies in the creative work of the
Ukrainian writer of the first third of the 19th century, Khrystia Alchevska (1882–1931). The
writer’s reflections of the trip to the Carpathians in 1906, which affected her world outlook,
is shown here. Facts of bringing representatives of different regions of Ukraine together
based on national literature are given in this article. The relations between the author and
Ivan Franko, Mykhailo Pavlyk and Olha Kobylyanska are described as well.